2020
DOI: 10.1111/opn.12307
|View full text |Cite
|
Sign up to set email alerts
|

Ageist attitudes among healthcare professionals and older patients in a geriatric rehabilitation facility and their association with patients' satisfaction with care

Abstract: Aim:The aim of this study was to explore the prevalence of ageist attitudes among older adults hospitalised in a geriatric rehabilitation facility, as well as the association between satisfaction with care and ageist attitudes. In addition, this study also explores the prevalence of ageist attitudes among healthcare professionals.Background: An ageist environment may potentially increase internalisation of stereotypes by older adults, which in turn may have a negative impact on care outcomes. Methods:In this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
10
0
7
Order By: Relevance
“…Abd El-Moniem, Mahfouz and Elsoued Hussein [22] found that 67.9% of hospitalized geriatric patients had moderate satisfaction levels regarding nursing care. Heyman, Osman and Natan's [23] study found that the satisfaction (treatment) of patients in geriatric rehabilitation facilities was high. The results of the study show that elderly patients are satisfied with nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Abd El-Moniem, Mahfouz and Elsoued Hussein [22] found that 67.9% of hospitalized geriatric patients had moderate satisfaction levels regarding nursing care. Heyman, Osman and Natan's [23] study found that the satisfaction (treatment) of patients in geriatric rehabilitation facilities was high. The results of the study show that elderly patients are satisfied with nursing.…”
Section: Discussionmentioning
confidence: 99%
“…Rush et al (35) stated in the integrative review in which they discussed nurses' attitudes toward older people, that attitudes toward older people were positively affected by experience. In a quantitative correlational study by Heyman, Osman & Ben Natan (36), they reported that health professionals who are specialized in working with older people exhibited a more positive attitude. It can be argued, based on the results obtained from this current study that being experienced in giving care for older people is effective in increasing awareness of nurses toward older people and developing positive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Turkish healthcare providers are reported to have generally positive attitudes towards older adults (Özdemir & Bilgili, 2016; Usta et al, 2012). However, it is known that negative ageist attitudes can lead to lower quality of care (Heyman et al, 2020) as well as increased burnout and decreased job satisfaction among care staff (Pekcetin, 2018a). Thus, researchers combat ageism with different methods such as cognitive behavioural therapy (Rababa et al, 2020) or nostalgia (Turner et al, 2018).…”
Section: Discussionmentioning
confidence: 99%